What you don't know about Charlie Outlaw - Stewart, Leah, 1973- (New York : G.P. Putnam's Sons, 2018)
After a series of missteps in the face of his newfound fame, actor Charlie Outlaw flees to a remote island in search of anonymity and a chance to reevaluate his recent breakup with his girlfriend, actress Josie Lamar. But soon after his arrival on the peaceful island, his solitary hike into the jungle takes him into danger he never anticipated
After a series of missteps in the face of his newfound fame, actor Charlie Outlaw flees to a remote island in search of anonymity and a chance to reevaluate his recent breakup with his girlfriend, actress Josie Lamar. Josie is getting ready for a fan-convention reunion of the cult show she was on years ago. When Charlie's solitary hike into the jungle takes him into danger he never anticipated, Josie needs to be a hero in real life to get him back
"A novel"--Cover
Includes bibliographical references
Keywords: Actors -- Fiction; Fame -- Fiction; Man-woman relationships -- Fiction; Kidnapping victims -- Fiction; Islands -- Fiction; Fame -- Fiction; Thrillers (Fiction); Novels